2008
DOI: 10.1016/j.immuni.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive B Cell Receptors Mimic Autonomous Pre-B Cell Receptor Signaling and Induce Proliferation of Early B Cells

Abstract: The majority of early immature B cells express autoreactive B cell receptors (BCRs) that are, according to the current view, negatively selected to avoid the production of self-reactive antibodies. Here, we show that polyreactive BCRs, which recognize multiple self-antigens, induced autonomous signaling and selective expansion of B cell precursors in a manner comparable to the pre-BCR. We found that the pre-BCR was capable of recognizing multiple self-antigens and that a signaling-deficient pre-BCR lacking the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
115
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 57 publications
2
115
0
Order By: Relevance
“…Whether this leakiness in tolerance induction is mediated directly by the pre-BCR, in that pre-B cells expressing an auto-reactive mH chains are deleted at the pre-BCR positive stage of development, or indirectly, by auto-reactive B cells escaping negative selection more readily in situations of reduced B-cell generation, as is the case in pre-BCR-deficient mice, is still open for clarification. However, the recent findings reported by Köhler et al [30] and van Loo et al [31] would, in our opinion, rather suggest that escape of auto-reactive B cells in surrogate light deficient mice is not directly mediated by the absence of the pre-BCR. Thus, Köhler et al showed that the pre-BCR is auto-reactive and is capable of recognizing multiple self-antigens [30].…”
Section: Tolerance Checkpoints In B-cell Development Large Pre-bii Cellsmentioning
confidence: 53%
See 3 more Smart Citations
“…Whether this leakiness in tolerance induction is mediated directly by the pre-BCR, in that pre-B cells expressing an auto-reactive mH chains are deleted at the pre-BCR positive stage of development, or indirectly, by auto-reactive B cells escaping negative selection more readily in situations of reduced B-cell generation, as is the case in pre-BCR-deficient mice, is still open for clarification. However, the recent findings reported by Köhler et al [30] and van Loo et al [31] would, in our opinion, rather suggest that escape of auto-reactive B cells in surrogate light deficient mice is not directly mediated by the absence of the pre-BCR. Thus, Köhler et al showed that the pre-BCR is auto-reactive and is capable of recognizing multiple self-antigens [30].…”
Section: Tolerance Checkpoints In B-cell Development Large Pre-bii Cellsmentioning
confidence: 53%
“…However, the recent findings reported by Köhler et al [30] and van Loo et al [31] would, in our opinion, rather suggest that escape of auto-reactive B cells in surrogate light deficient mice is not directly mediated by the absence of the pre-BCR. Thus, Köhler et al showed that the pre-BCR is auto-reactive and is capable of recognizing multiple self-antigens [30]. This auto-reactivity seems to be mainly mediated by the non-Ig region of the surrogate light chain component l which corresponds to the same region previously shown to mediate cell autonomous pre-BCR signaling [32].…”
Section: Tolerance Checkpoints In B-cell Development Large Pre-bii Cellsmentioning
confidence: 53%
See 2 more Smart Citations
“…Furthermore, findings of interaction between the pre-BCR and galectin-1 (14) and binding of the non-Ig tail of l5 to stromal cell-associated heparan sulfate (15) would support this notion. The pre-BCR is polyreactive and capable of recognizing multiple (self-)Ags including DNA, LPS, and insulin, via the non-Ig tail of l5 (16). Thus, pre-BCR autoreactivity may serve to clonally expand those cells that produce a functional IgH m chain and ensures that this selection can occur in the absence of foreign Ags.…”
Section: /2mentioning
confidence: 99%